Novel MSVPWM to Reduce the Inductor Current Ripple for Z-Source Inverter in Electric Vehicle Applications - Qianfan Zhang; Shuai Dong; Ping Xue; Chaowei Zhou; ShuKang Cheng (The Scientific World Journal)
A novel modified space vector pulse width modulation (MSVPWM) strategy for Z-Source inverter is presented. By rearranging the position of shoot-through states, the frequency of inductor current ripple is kept constant. Compared with existing MSVPWM strategies, the proposed approach can reduce the maximum inductor current ripple. So the volume of Z-source network inductor can be designed smaller, which brings the beneficial effect on the miniaturization of the electric vehicle controller. Theoretical findings in the novel MSVPWM for Z-Source inverter have been verified by experiment results.